Assessing Wolbachia circulation in wild populations of phlebotomine sand flies from Spain and Morocco: implications for control of leishmaniasis - Andrés Torres-Llamas; Victoriano Díaz-Sáez; Manuel Morales-Yuste; Patricia Ibáñez-De Haro; Arturo Enrique López-López; Victoriano Corpas-López; Francisco Morillas-Márquez; Joaquina Martín-Sánchez (Parasites & Vectors)
Abstract Background Vector-borne diseases such as leishmaniasis exert a huge burden of morbidity and mortality that are mainly controlled through vector control. The increasing threat of insecticide-resistant vectors entails incorporating more vector control interventions to eliminate these diseases. Introduction of Wolbachia into wild vector populations has been suggested as a potential vector control measure that would require extensive regional knowledge. The aim of this work is to estimate the prevalence of Wolbachia infection and monitor circulating strains in wild sand fly populations from Spain and Morocco, two countries where leishmaniasis is endemic. Methods Wolbachia was detected using polymerase chain reaction (PCR). Haplotype diversity was performed by sequencing, and phylogenetic relationships were then established. In silico prediction of the Wolbachia surface protein (WSP) structures was performed. To investigate the relationship between epidemiological variables and the presence of Wolbachia, regression analyses were employed. Results Wolbachia was detected in 45.8% of the specimens tested (319/697), and similar infection rates were found (P = 0.92) in males (46.1%; 94/204) and females (45.6%; 225/493). Differences in infection were detected among Spanish sand fly species (P < 0.001), being higher for Phlebotomus papatasi (35/52) and Phlebotomus perniciosus (239/384). No infected Phlebotomus sergenti specimens were found in Spain, whereas two different Wolbachia haplotypes were detected in P. sergenti sand flies from Morocco. No significant differences were found between sex, species, or capture sites in specimens captured in Morocco (P > 0.05). Five Wolbachia haplotypes distributed in the known A and B supergroups were identified. Structural analysis showed a nine-amino acid insertion in the fourth loop of a Wolbachia haplotype found in P. sergenti specimens from El Borouj (Morocco). Conclusions We confirmed the circulation of different Wolbachia strains in all sand fly species investigated. All L. infantum proven or suspected vectors shared the same, or a closely related, Wolbachia haplotype. The haplotype bearing the loop insertion was found in the locality undergoing an anthroponotic cutaneous leishmaniasis outbreak. These extracellular loops might have some role in enhancing or inhibiting the development of Leishmania and other pathogens in sand flies. These findings are very promising and highlight the need to further investigate the tripartite interactions between Wolbachia strain, Leishmania species, and sand fly species/lineage. Graphical Abstract